Growth of Pinus arizonica Engelm. plants inoculated with Pisolithus tinctorius and Astraeus hygrometricus under greenhouse conditionsCrecimiento de plantas de Pinus arizonica Engelm. inoculadas con Pisolithus tinctorius y Astraeus hygrometricus en invernaderoMiroslava Quiñónez-Martínez¹*; Liliana de J. Gómez-Flores¹; Fortunato Garza-Ocañas²; José Valero-Galván¹; Jesús A. Nájera-Medellín¹1Universidad Autónoma de Ciudad Juárez. Av. Benjamín Franklin núm. 4650, zona PRONAF. C. P. 32310. Ciudad Juárez, Chihuahua, México.²Universidad Autónoma de Nuevo León, Facultad de Ciencias Forestales. Carretera Nacional km 145. Linares, Nuevo León, México.*Corresponding author: mquinone@uacj.mx; tel.: +526561764459.Received: August 9, 2022 / Accepted: March 15, 2023AbstractIntroduction: Ectomycorrhizal associations are an essential component of nutrient cycling and forest health.Objective: To evaluate the effects of spore inoculation of Pisolithus tinctorius (Pers.) Coker & Couch and Astraeus hygrometricus (Pers.) Morgan on Pinus arizonica Engelm. growth.Materials and methods: Three mycorrhizal inoculation treatments (A. hygrometricus, P. tinctorius and Ectorrize®) were applied with three volumes (10, 25 and 50 mL: 106 spores∙mL-1) and a control group with no inoculum. The variables measured were mycorrhizal survival and colonization; plant height; shoot length and diameter; root length and biomass. The ectomycorrhizas were characterized and a mineral analysis of nutritional elements in the shoot and root was performed. The effects of fungal species and inoculum volume were determined by randomized ANOVA (α = 0.05).Results and discussion: The volume of this inoculum had no significant effect (P > 0.05) on the variables, but there were differences between the fungal species and the control (P > 0.05); with P. tinctorius having the greatest significant effect. Inoculated plants had higher survival rate and higher amount of minerals in the composition compared to non-inoculated plants (P > 0.05). The ectomycorrhizas showed clear morphological differences; the Hartig net was observed as an indicator.Conclusion: Inoculation with the ectomycorrhizal fungi improved the morphological development of P. arizonica. The smallest inoculum dose (10 mL: 106 spores∙mL-1) is recommended, mainly of the fungus P. tinctorius.ResumenIntroducción: Las asociaciones ectomicorrícicas son un componente esencial para el ciclo de nutrientes y la salud del bosque.Objetivo: Evaluar los efectos de la inoculación de esporas de los hongos ectomicorrícicos Pisolithus tinctorius(Pers.) Coker & Couch y Astraeus hygrometricus (Pers.) Morgan sobre el crecimiento de Pinus arizonica Engelm.Materiales y métodos: Se aplicaron tres tratamientos de inoculación fúngica (A.hygrometricus, P. tinctorius y Ectorrize®) con tres volúmenes (10, 25 y 50 mL: 106 esporas∙mL-1) y un grupo control sin inóculo. Las variables medidas fueron supervivencia y colonización micorrícica; altura de la planta; longitud y diámetro del follaje; longitud de la raíz y biomasa. Las ectomicorrizas se caracterizaron y se hizo un análisis mineral de elementos nutricionales en el sistema aéreo y radicular. Los efectos de las especies fúngicas y el volumen del inóculo se determinaron mediante un ANOVA aleatorizado (α = 0.05).Resultados y discusión: El volumen de inoculante no tuvo efecto significativo (P > 0.05) sobre las variables, pero sí hubo diferencias entre la especie fúngica y el control (P ≤ 0.05); siendo P. tinctorius el de mayor efecto significativo. Las plantas inoculadas tuvieron mayor tasa de supervivencia y mayor cantidad de minerales en la composición en comparación con las no inoculadas (P ≤ 0.05). Las ectomicorrizas mostraron claras diferencias morfológicas; se observó la red de Hartig como indicador. Conclusión: La inoculación con los hongos ectomicorrícicos causó mejoras en el desarrollo morfológico de P.arizonica. Se recomienda la dosis más pequeña de inóculo (10 mL: 106 esporas∙mL-1), principalmente del hongo P. tinctorius. Scientific paperhttps://doi.org/10.5154/r.rchscfa.2022.08.053Please cite this article as follows (APA 7): iroslava Quiñónez-Martínez¹*; Gómez-Flores, L. J., Garza-Ocañas, F., Valero-Galván, J., & Nájera-Medellíno, J. A. (2023) Growth of Pinus arizonica Engelm. plants inoculated with Pisolithus tinctorius and Astraeus hygrometricus under greenhouse conditions. Revista Chapingo Serie Ciencias Forestales y del Ambiente, 29(2), 99-118. https://doi.org/10.5154/r.rchscfa.2022.08.053https://revistas.chapingo.mx/forestalesKeywords: ectomycorrhizae; mineral analysis; symbiosis; Ectorrize; mycorrhizal system.Palabras clave: ectomicorrizas; análisis mineral; simbiosis; Ectorrize; sistema micorrícico.PUBLICACIÓN EN AVANZADA - Quiñonez Martínez, Miroslava (2023)
Inoculation with ectomycorrhizal fungi (EMF) improved the growth of P. arizonica Plants inoculated with EMF had higher survival and higher mineral content EMF can establish ymbiosis with P. arizonica at low inoculation volumes The smallest dose of EMF (10 mL: 106 spores∙mL-1) is recommended on P. arizonica